A share in pain and passion: the women of Synge's plays - Finn, Stephen Michael (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1974)
Synge's plays contain some of the most arresting figures in modern drama, his characterization second only to his unique language, the most striking feature of his writing. Of the men, only Christy Mahon and Martin Doul stand out but the women form a brilliant company usually overshadowing the other characters. Chapter 1, p. 1.
Keywords: Synge, J. M. (John Millington), 1871-1909; English literature -- Irish authors -- History and criticism; English drama -- Irish authors -- History and criticism